Tumor formation and antitumor immunity; the overlooked significance of histamine. Issue 2 (5th June 2014) - Falus, Andras; Gilicze, Anna
Abstract : Review on histamine as a relevant player in the generation and maintenance of tumors and anti-tumor responses. Abstract: HA is a biogenic amine, widely distributed throughout the body. Given the observations that HA, the decarboxylated amino acid histidine, can be induced and made available in an unstored, diffusible form in tissues undergoing rapid growth (such as tumors and regenerating tissues), it could have a role in antitumor response beyond the well-studied inflammatory and allergic responses.